2016
DOI: 10.3390/metabo6040041
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Infection Reduces Nutrition Uptake and Nucleotide Biosynthesis in a Human Airway Epithelial Cell Line

Abstract: Abstract:The Gram positive opportunistic human pathogen Staphylococcus aureus induces a variety of diseases including pneumonia. S. aureus is the second most isolated pathogen in cystic fibrosis patients and accounts for a large proportion of nosocomial pneumonia. Inside the lung, the human airway epithelium is the first line in defence with regard to microbial recognition and clearance as well as regulation of the immune response. The metabolic host response is, however, yet unknown. To address the question o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…In addition, we also observed activation of both AMPK and ERK signaling pathways in HeLa cells after MRSA infection. In accordance with these findings, a recent study has shown that the levels of ATP in human alveolar epithelial cells were significantly decreased during early time points of S. aureus infection ( 74 ), further pointing to a starvation-induced response. Crucially, once we inhibited the host AMPK pathway using dorsomorphin, intracellular MRSA survival was significantly hampered and autophagy levels were decreased, supporting our hypothesis that the activation of autophagy is caused by the state of starvation induced by the intracellular pathogen, and this autophagy benefits the intracellular survival of MRSA.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, we also observed activation of both AMPK and ERK signaling pathways in HeLa cells after MRSA infection. In accordance with these findings, a recent study has shown that the levels of ATP in human alveolar epithelial cells were significantly decreased during early time points of S. aureus infection ( 74 ), further pointing to a starvation-induced response. Crucially, once we inhibited the host AMPK pathway using dorsomorphin, intracellular MRSA survival was significantly hampered and autophagy levels were decreased, supporting our hypothesis that the activation of autophagy is caused by the state of starvation induced by the intracellular pathogen, and this autophagy benefits the intracellular survival of MRSA.…”
Section: Discussionsupporting
confidence: 73%
“…However, some of the cellular responses that occur in ARDS can be inferred from studying cultured human cell models. For example, the effect of bacterial infection on the metabolome of A549 cultured human airway epithelial cells (mimics an infection-related direct lung injury) demonstrated an increase in extracellular secretion of glutamate and pyruvate (28). The study also revealed that concentrations of glycine, aspartate, and alanine were increased in the extracellular space suggesting a reduction in the cellular usage of these amino acids with consequent intracellular overflow and secretion (28).…”
Section: Metabolomics Studies Of Ardsmentioning
confidence: 99%
“…Moreover, host cholesterol import is required by intracellular Mycobacterium tuberculosis to persist inside both macrophages and mice lungs [88]. On the other hand, a reduction in nutrient uptake as well as nucleotide biosynthesis has been recently observed in human airway epithelial cells infected with S. aureus [89].…”
Section: Host-directed Therapies: a Novel Perspectivementioning
confidence: 99%